Blocks. The clue to dynamic aspects of logic - Batens, Diderik (Logique et Analyse, 1995)
The present paper introduces a new approach to formal logic. The block approach is especially useful to grasp dynamic aspects of reasoning, including formal reasoning, that fall beyond the reach of the usual approaches. A block language, the block analysis of proofs, and semantic systems in terms of blocks are articulated. The approach is first applied to classical logic (including proof heuristics). It is used to solve two important problems for adaptive logics (that have a dynamic proof theory). Some further applications are discussed, including meaning change.
Appeared 1997